Methylmercury cytotoxicity and possible mechanisms in human trophoblastic HTR-8/SVneo cells - Ying Liao (Ecotoxicology and Environmental Safety, 2021)
Methylmercury (MeHg) exposure during pregnancy can lead to adverse outcomes, including miscarriage and intrauterine growth retardation. In this study, MeHg cytotoxicity and its mechanisms in HTR-8/SVneo cells were investigated. MeHg inhibited HTR-8/SVneo cell viability and severely disrupted the cellular submicrostructure, showing a time-dose effect relationship. After MeHg treatment, the reactive oxygen species levels, malondialdehyde content, and superoxide dismutase (SOD) and catalase activities in the HTR-8/SVneo cells increased significantly with increased MeHg concentration (P<0.05). Similarly, MeHg also induced HTR-8/SVneo cell apoptosis in a dose-dependent manner. The proportion of cells in G1 phase decreased with increasing MeHg concentration, while that in the S and G2/M phases gradually increased. Moreover, cell migration and invasion capacities gradually decreased with increasing MeHg concentration, showing a significant difference between the MeHg-treated and control groups. Genes related to oxidative stress (HSPA6, HSPA1A, Nrf2, SOD1, HO-1, NQO1, OSGIN1, and gPX1), cell cycle (P21 and CDC25A), apoptosis (CYCS and AIFM2), and migration and invasion (CXCL8, CXCL3, CLU, IL24, COL3A1, MAPT, and ITGA7) were differentially expressed in the MeHg-treated group, indicating MeHg toxicity and mechanism of action. This study will provide insights into the prevention and treatment of pregnancy-related diseases caused by MeHg.